Optimal Power Flow using Ant Colony Search Algorithm to Evaluate Load Curtailment Incorporating Voltage Stability Margin Criterion - Lenin Kanagasabai; B. Ravindranath Reddy; M. Surya Kalavathi (Institute of Advanced Engineering and Science, 2013)
This paper proposes a method to compute load curtailment evaluation using ACSA based optimal power flow incorporating voltage stability margin criterion. . In a deregulated environment, congestion alleviation could mean load curtailment in certain situations. The utilities would definitely prefer to curtail a load as lower as possible during a viability crisis situation. A criterion based on the voltage stability indicator is them incorporated as an additional constraint into the optimal power flow using ACSA algorithm and it is evaluated in a WSCC 9-bus test system.DOI:http://dx.doi.org/10.11591/ijece.v3i5.2738